Venous thromboembolism has the same risk factors as atherosclerosis: A PRISMA-compliant systemic review and meta-analysis. Issue 32 (August 2016) - Mi, Yuhong; Yan, Shufeng; Lu, Yanhui; Liang, Ying; Li, Chunsheng
Abstract: Background: Previous studies have shown that idiopathic pulmonary embolism is positively associated with other cardiovascular events, such as myocardial infarction and stroke, suggesting a potentially important association between atherosclerosis risk factors and venous thromboembolism (VTE). We performed a meta-analysis to evaluate the correlation between risk factors for atherosclerosis and VTE. Methods: In December 2014, we searched MEDLINE and EMBASE for studies evaluating the associations between VTE and risk factors for atherosclerosis and pooled outcome data using random-effects meta-analysis. In addition, we analyzed publication bias. Results: Thirty-three case-control and cohort studies with a total of 185, 124 patients met the inclusion criteria. We found that participants with body mass index (BMI) ≥30 kg/m 2 had a significantly higher prevalence of VTE than those with BMI <30 kg/m 2 in both case-control studies (odds ratio [OR] = 2.45, 95% confidence interval [CI]: 1.78–3.35) and cohort studies (relative risk [RR] = 2.39, 95% CI: 1.79–3.17). VTE was more prevalent in patients with hypertension than without hypertension (OR = 1.40, 95% CI: 1.06–1.84; RR = 1.36, 95% CI: 1.11–1.67). The findings were similar for VTE prevalence between patients with and without diabetes (OR = 1.78, 95% CI: 1.17–2.69; RR = 1.41, 95% CI: 1.20–1.66). Current smoking was significantly associated with VTE prevalence in case-control studies (OR = 1.34, 95% CI: 1.01–1.77), but not in cohort studies (RR = 1.29, 95% CI: 0.96–1.72). In addition, we found that total cholesterol and triglyceride concentrations were significantly higher in patients with VTE than without VTE (weighted mean differences [WMD] = 8.94 mg/dL, 95% CI: 3.52–14.35 mg/dL, and WMD = 14.00 mg/dL, 95% CI: 8.85–19.16 mg/dL, respectively). High-density lipoprotein cholesterol concentrations were significantly lower in patients with VTE than without VTE (WMD = −2.03 mg/dL, 95% CI: −3.42 to −0.63 mg/dL). Higher quality studies were more homogeneous, but confirmed the same significant associations. Conclusions: Based on our systematic review and meta-analysis, we observed a significant association between VTE and the risk factors for atherosclerosis. These results may make an important contribution to clinical practice regarding VTE treatment. Abstract : Supplemental Digital Content is available in the text